Diagnostic Tests Based on Three Level Tests on Fixed Materials for Students with Misconceptions - Theis, Roseli; Junita, Ranisa; Kamid; Iriani, Dewi (Jurnal Pendidikan Indonesia, 2022)
Misconception is something that can hinder the acceptance of new material and affect success in solving math problems. This study aims to develop a Three-Tier diagnostic test to identify misconceptions. The development of this test aims to identify the types of errors in the set and describe the quality of this diagnostic test. The research conducted was the plomp development model research, which is a model widely used for the development of educational products such as teaching materials, media, or learning approaches. The population in this study were students of mathematics education. Data analysis performed included validity, reliability, level of difficulty, discriminating power, questionnaire analysis, interpretation of three-level multiple-choice diagnostic test results, and profile analysis of students' understanding of students. The results of this study obtained a diagnostic test that can find out conceptual errors in students who have been tested for validity and declared valid. So that it can be concluded that the diagnostic test instrument for the set material in this study includes; diagnostic test grids, diagnostic test questions, answer key sheets and diagnostic test rubrics, diagnostic test answer sheets, diagnostic test kit validation sheets, diagnostic test sheets have been generated.